15.2k views
5 votes
Consider the differential equation
y - 4 y^(2) = ( y^(7)+1x)y' where y(0)=1 Solve this equation by the following method: First, find a suitable integrating factor to obtain an implicit solution F(x,y) = C. This implicit solution cannot be solved explicitly for y but it can be solved explicitly for x.

1 Answer

4 votes
You have


\underbrace{(y-4y^2)}_M\,\mathrm dx-\underbrace{(y^7+x)}_N\,\mathrm dy=0

with partial derivatives


M_y=1-8y

N_x=-1

An integrating factor in terms of
y is easy to find:


\mu(y)=\exp\left(\displaystyle\int\frac{N_x-M_y}M\,\mathrm dy\right)

\mu(y)=\exp\left(\displaystyle\int(8y-2)/(y-4y^2)\,\mathrm dy\right)

\implies\mu(y)=\frac1{y^2}

Distributing
\mu(y) across the ODE gives


\underbrace{(y-4y^2)/(y^2)}_(M^*)\,\mathrm dx-\underbrace{(y^7+x)/(y^2)}_(N^*)\,\mathrm dy=0

with partial derivatives


{M^*}_y=-\frac1{y^2}

{N^*}_x=-\frac1{y^2}

so the modified ODE is exact.

Now,


F_x(x,y)=M^*(x,y)

F(x,y)=\displaystyle\int(y-4y^2)/(y^2)\,\mathrm dx

F(x,y)=\left(\frac1y-4\right)x+f(y)


F_y(x,y)=N^*(x,y)

-\frac x{y^2}+f'(y)=-y^5-\frac x{y^2}

f'(y)=-y^5

\implies f(y)=-\frac16y^6+C

and so the general solution is


F(x,y)=\left(\frac1y-4\right)x-\frac{y^6}6=C

Solving explicitly for
x, we have


x=\frac{C+\frac{y^6}6}{\frac1y-4}=(Cy+y^7)/(6-24y)
User B Robster
by
5.6k points